Taking your first shot a woman's introduction to defensive shooting and personal safety - Finch, Lynne (Skyhorse Publishing, 2013)
Numbers don't lie; more and more women are purchasing guns and learning to shoot! While shooting used to be a male-dominated sport, women across the country have begun discovering that a trip to the range not only is relaxing, but also brings with it a sense of strength and empowerment. Taking Your First Shot is an introductory guide perfect for either those stepping out onto the range for the first time or those looking to brush up on their skills. Author Lynne Finch coaches women on the decision to learn to shoot, how to find formal training, selecting and purchasing a handgun